Effect of FeB additions on sintering characteristics of injection moulded 17-4PH stainless steel powder - (:unkn) unknown (KLUWER ACADEMIC PUBL, 2004)
High density sintering of precipitation hardening stainless steel such as 17-4 PH involves a combination of relatively high temperature (>1350degreesC) and extended sintering time. In this study, the effect of addition of FeB on sintering characteristics of 17-4 PH stainless steel was investigated. Addition of boron is promoted to get highly dense sintered steels. The amount of boron plays a role in determining the sintered microstructure and properties. With the increased amount of FeB sintered density and tensile strength increase while sintering time and temperature decrease. (C) 2004 Kluwer Academic Publishers.
Keywords: MECHANICAL-PROPERTIES; MICROSTRUCTURE; DENSIFICATION